It's that vision thing: Why the bailouts aren't working, and why a new financial system is needed - Jan Kregel (Levy Economics Institute of Bard College, 2009)
The Federal Reserve's response to the current financial crisis has been praised because it introduced a zero interest rate policy more rapidly than the Bank of Japan (during the Japanese crisis of the 1990s) and embraced massive quantitative easing. However, despite vast capital injections, the banking system is not lending in support of the private sector. Senior Scholar Jan Kregel compares the current situation with the Great Depression, and finds an absence of New Deal measures and institutions in the current rescue packages. The lessons of the Great Depression suggest that any successful policy requires fundamental structural reform, an understanding of how the financial system failed, and the introduction of a new financial structure (in a short space of time) that is designed to correct these failures. The current crisis could have been avoided if increased household consumption had been financed through wage increases, says Kregel, and if financial institutions had used their earnings to augment bank capital rather than bonuses.
Keywords: 330